To vaccinate or not: literacy against hesitancy: Vaccination hesitancy - Karaboue, Michele Ahmed Antonio; Ferrara, Michela; Bertozzi, Giuseppe; Berritto, Daniela; Volonnino, Gianpietro; La Russa, Raffaele; Lacasella, Giorgia Viola (Medicina Historica, 2022)
Background: Vaccines currently represent the most efficient tool to prevent the spread of potentially life-threatening infectious diseases. However, in the Western world, the widespread nature of vaccinations has led to a reduction in the incidence of these diseases, with a consequent progressive decline in vaccination practice. This phenomenon is further fueled by the anti-vaccine movements which today find fertile ground thanks to the rapid dissemination of information through social media. The present review focuses on three different vaccination target groups, pregnant women, parents, and healthcare professionals, in order to analyze vaccine hesitancy factors and suggest strategies aimed at improving vaccination empowerment.Methods: The literature search was conducted on the PubMed database using the keywords “vaccine hesitancy”, “mandatory vaccination”, “vaccine acceptance”, “vaccination barriers”, “vaccine AND pregnancy”, “vaccine AND healthcare workers”, “vaccine AND parents”. Only publications in English and Italian were selected. A total of 51 articles were selected for this narrative review in relation to their relevance to the topic under study. Discussion and conclusion: This review highlights the heterogeneity of the reasons behind vaccine hesitancy. Poor adherence to vaccinations should not be interpreted exclusively as an unconditional refusal but rather as an indicator of the lack of information provided by health professionals. In this perspective, a need emerges to strengthen the therapeutic alliance between healthcare workers and patients. Considering the low vaccination coverage rates among health professionals, programs aimed at implementing both their vaccine education and trust in healthcare systems are essential.